Automotive Meets Electronics : 10. - 11.03.2021, online ([VDE Verlag GmbH], 2021)
Long description: In the same way as time will be subject to permanent changes, the focus of the AmE Conference is going to change. More than ten years ago, when the AmE Conference was launched, automotive electronics was characterized by a continuously growing network of many dedicated ECUs. Looking at today's technology and changing requirements, particularly in communication, we see that mobility turns out to become a service rather than a means of transport. Intermodal travelling is in the transition from vision to reality, and car sharing is no longer the dream of lunatics - it has rather become a viable option for many people, especially in combination with electric vehicles. These changes imply changes in automotive technology and development methodologies. The architecture is in transition from a heterogenous network of ECUs towards a centralized system with high computational power. These new systems are built with new technologies and require new development and simulation tools for handling the complexity. The current software development will continue regarding many safety relevant domains, but new approaches such as Artificial Intelligence/Machine Learning will enter the stage due to the necessity to handle the huge amounts of data, generated by sensors and the link to the backbone servers providing additional information.